Lipids : structure, physical properties and functionality - Larsson, Kare, 1937- (Oily Press lipid library, 2006)
In Lipids: Structure, Physical Properties and Functionality, Professor Kire Larsson, Peter Quinn, Kiyotaka Sato and Fredrik Tiberg have provided an up-to-date description of the diversity of lipid molecular arrangements in different physical states as a basis for the understanding of lipid functionality in biological and technical systems. Lipids are components of many complex systems, some of which are natural in origin, such as the cell membranes of living organisms, and others created by human intervention, such as food emulsions. Scientists and technologists working on complex systems containing lipids need to relate composition and structure to behaviour, whether this is in the formulation of food products, development of drugs and drug delivery systems, study of living cells, or creation of new cosmetics, to name a few examples. This book was originally planned as a new edition to Kire Larsson's popular book Lipids: Molecular Organization, Physical Functions and Technical Applications published by the Oily Press in 1994. However, the subject area had to be expanded to such an extent that the one author could no longer cover it. Instead of resorting to the usual edited book with each chapter written by a different author, the three well-known scientists named above were invited to act as co-authors with Kire Larsson. As a result Lipids: Structure, physical properties and functionality is not a second edition, but a new book with a new ISBN number.